Anatomical, functional and metabolic imaging of radiation‐induced lung injury using hyperpolarized MRI. (25th August 2014) - Santyr, Giles; Fox, Matthew; Thind, Kundan; Hegarty, Elaine; Ouriadov, Alexei; Jensen, Michael; Scholl, Timothy J.; Van Dyk, Jacob; Wong, Eugene; Rizi, Rahim R.
<x xml:space="preserve">Abstract</x> MRI of hyperpolarized 129Xe gas and 13C‐enriched substrates (e.g. pyruvate) presents an unprecedented opportunity to map anatomical, functional and metabolic changes associated with lung injury. In particular, inhaled hyperpolarized 129Xe gas is exquisitely sensitive to changes in alveolar microanatomy and function accompanying lung inflammation through decreases in the apparent diffusion coefficient (ADC) of alveolar gas and increases in the transfer time (Ttr) of xenon exchange from the gas and into the dissolved phase in the lung. Furthermore, metabolic changes associated with hypoxia arising from lung injury may be reflected by increases in lactate‐to‐pyruvate signal ratio obtained by magnetic resonance spectroscopic imaging following injection of hyperpolarized [1‐13C]pyruvate. In this work, the application of hyperpolarized 129Xe and 13C MRI to radiation‐induced lung injury (RILI) is reviewed and results of ADC, Ttr and lactate‐to‐pyruvate signal ratio changes in a rat model of RILI are summarized. These results are consistent with conventional functional (i.e. blood gases) and histological (i.e. tissue density) changes, and correlate significantly with inflammatory cell counts (i.e. macrophages). Hyperpolarized MRI may provide an earlier indication of lung injury associated with radiotherapy of thoracic tumors, potentially allowing adjustment of treatment before the onset of severe complications and irreversible fibrosis. Copyright © 2014 John Wiley & Sons, Ltd.